Intensification of field practice process while training qualified workers of construction profile - Mikhniuk, M (Professional Pedagogics, 2011)
The article discusses conditions resulting on intensification of vocational training of construction profile qualified workers.
Keywords: intensification conditions; competence, active methods of training; cognitive activity